Online Shop Transaction Analysis View From Sharia Compliance (Case Study Of Faculty Students Economy And Business Islam Iain Padangsidimpuan ) - Hutagalung, Muhammad Wandisyah; Aini, Ihdi; Damisah, Arti; Harahap, Nazmi Darmawanti (Journal of Islamic Financial Technology, 2022)
This research is motivated by the many occurrences of incompatibility of goods ordered with those sent in online shop transactions among students of the Islamic Banking Study Program FEBI IAIN Padangsidimpuan. So the purpose of this study is to find out the perceptions of students of the Islamic Banking Study Program FEBI IAIN Padangsidimpuan about online shops , the form of online shop practice for students of the Islamic Banking Study Program FEBI IAIN Padangsidimpuan, and the concept of online shop seen from fiqh . This research uses descriptive qualitative analysis method . Sources of data used are primary data and secondary data, these data were obtained from information researchers by using direct interviews with research subjects. While the data analysis technique uses data reduction, data presentation, and drawing conclusions. From the results of the study, it can be seen that the perceptions of students of the Islamic Banking Study Program FEBI IAIN Padangsidimpuan about online shop transactions has both positive and negative sides. The positive side can make it easier for students to make buying and selling, save time, energy, can be done using a smartphone . While the negative side is shopping online , not being able to try the goods directly, incurring shipping costs, delays in delivery times, and rampant fraud.Keywords: Buying and Selling, Online Shop, As-Salam